2007
DOI: 10.3748/wjg.v13.45.6053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bcl-2 and Bax on survival of side population cells from hepatocellular carcinoma cells

Abstract: AIM:To understand the role and significance of side population (SP) cells from hepatocellular carcinoma (HCC) in hepatocarcinogenesis, development, relapse and metastasis, we simulated the denutrition conditions that cancer cells experience in clinical therapy, observed the different anti-apoptosis ability of SP cells and non-SP cells under such conditions, and established the possible effects of P53, Bcl-2 and Bax on survival of SP cells. METHODS:We used flow cytometry to analyze and sort the SP and non-SP ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Bcl-2 gene family is essential for cell apoptosis regulation, where Bcl-2 acts as an anti-apoptosis factor and Bax as an pro-apoptosis factor [19]. In a recent study, the up-regulated Bcl-2 and down-regulated Bax were effective in side population cells during anti-apoptosis in hepatocarcinogenesis, which indicated that up-regulated Bcl-2 had a direct relationship with down-regulated Bax and increased anti-apoptosis ability in side population cells [20]. As reflected in our study, expressions of p21 and p53 were increased, while expressions of Cyclin E and CDK2 were decreased in the PAK1 shRNA group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bcl-2 gene family is essential for cell apoptosis regulation, where Bcl-2 acts as an anti-apoptosis factor and Bax as an pro-apoptosis factor [19]. In a recent study, the up-regulated Bcl-2 and down-regulated Bax were effective in side population cells during anti-apoptosis in hepatocarcinogenesis, which indicated that up-regulated Bcl-2 had a direct relationship with down-regulated Bax and increased anti-apoptosis ability in side population cells [20]. As reflected in our study, expressions of p21 and p53 were increased, while expressions of Cyclin E and CDK2 were decreased in the PAK1 shRNA group.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the downregulation of CDK4/(and CDK6)/D-type cyclin complexes and CDK2/cyclin E (and cyclin A) complexes mediate p21dependent inhibition of cell cycle progression from G1 to S phases [22]. P53, the most common mutated gene in human malignancies, was named the "guardian of the genome" [20]. According to the previous study, p21 WAF1/CIP1 expression seems to be mainly associated with altered p53 in HCV-related HCC and malignant progression of HCC was due to the block of the p53-p21 WAF1/CIP1 cell cycleregulating pathway [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have shown that silencing of the Nrf2 gene expression attenuated the expression of ABCG2, Bcl-2 and Bmi-1, rendering the SP cells more sensitive to drug treatment and efficiently subjected to apoptosis. There is a high risk of alteration in programmed cell death during carcinogenesis associated with mutation in the p53 gene and modulation of apoptotic regulatory Bcl-2, Bmi-1 and Bax proteins in cervical CSCs (18). Inactivation of the p53 gene induces the production of other pro-apoptotic proteins such as Bax and represses the anti-apoptotic factors such as Bcl-2 and Bmi-1 (18).…”
Section: Discussionmentioning
confidence: 99%
“…There is a high risk of alteration in programmed cell death during carcinogenesis associated with mutation in the p53 gene and modulation of apoptotic regulatory Bcl-2, Bmi-1 and Bax proteins in cervical CSCs (18). Inactivation of the p53 gene induces the production of other pro-apoptotic proteins such as Bax and represses the anti-apoptotic factors such as Bcl-2 and Bmi-1 (18). Therefore, we hypothesized that an elevated level of Nrf2 may be involved in the inactivation of the p53 gene and its function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation